2015
DOI: 10.1615/jenvironpatholtoxicoloncol.2015013477
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Leukemia/Lymphoma-Related Factor Protein Expression Inhibits Glioma Cell Proliferation and Invasion

Abstract: Overexpression of leukemia/lymphoma-related factor (LRF), which is an erythroid myeloid ontogenic factor protein, occurs in different cancers, including glioma. LRF is also reported to have an oncogenic activity in various human cancers. This study investigated the effect of LRF knockdown on the regulation of glioma growth. LRF short hairpin RNA (shRNA) suppressed the expression of LRF protein in a glioma cell line (GL261-EGFP) compared to the negative control vector-transfected glioma cells. LRF knockdown als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Published data indicate that LRF is associated with the pathogenesis of malignant tumours . We wondered if LRF was also expressed in Cca cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data indicate that LRF is associated with the pathogenesis of malignant tumours . We wondered if LRF was also expressed in Cca cells.…”
Section: Resultsmentioning
confidence: 99%
“…Published data indicate that LRF is associated with the pathogenesis of malignant tumours. 14 We wondered if LRF was also expressed in Cca cells. To test this, we analysed human Cca cell lines, the LIM1215 and HCT116 cells, by RT-qPCR and Western blotting.…”
Section: Activation Of Par2 Increases the Expression Of Lrf In Cca mentioning
confidence: 99%
“…However, LRF/ ZBTB7A association with cancer progression goes far beyond hematological cancers. After the initial report associating LRF/ ZBTB7A with T cell lymphoblastic lymphoma/leukemia through the suppression of the Arf tumor suppressor ( p19 Arf ) gene and the consequent decrease of p53 activity [38], accumulating evidence further show that LRF/ ZBTB7A is overexpressed in several other human cancers, including non-small cell lung cancer (NSCLC) [40–43], hepatocellular carcinoma [4448], prostate [49, 50], ovarian [51], breast [5254] and gastric cancers [55], glioma [56], sarcomas [57, 58], colorectal cancer [5962], and renal carcinoma [63]. Further elucidation of these oncogenic functions revealed that LRF/ ZBTB7A can influence cancer cell survival and proliferation, apoptosis, invasion and migration/metastasis, traits comprising some of the key biological capabilities required for the multistep development of human cancer, also presented as “hallmarks of cancer” [64].…”
Section: Introductionmentioning
confidence: 99%
“…These data highlighted not only the diversity of its roles but also their context-dependency. Cell cycle-related genes are frequent targets of LRF/ ZBTB7A [48, 56, 57, 59, 6567], offering a mechanistic explanation of the factor’s ability to affect cell proliferation. In human hepatocellular carcinoma cell lines, LRF/ ZBTB7A regulates cell cycle progression by either suppressing or promoting the expression of key cell cycle regulators like cyclin-dependent kinase inhibitors 2B, 1B, and 1A ( p15, p27, and p21 genes, respectively), tumor protein p53 ( TP53 ), CYCLIN D1, CYCLIN D3, and cyclin-dependent kinases CDK4 and CDK6.…”
Section: Introductionmentioning
confidence: 99%